Advances in biomineralization-inspired materials for hard tissue repair - Shuxian Tang; Zhiyun Dong; Xiang Ke; Jun Luo; Jianshu Li (Nature Publishing Group, 2021)
Abstract Biomineralization is the process by which organisms form mineralized tissues with hierarchical structures and excellent properties, including the bones and teeth in vertebrates. The underlying mechanisms and pathways of biomineralization provide inspiration for designing and constructing materials to repair hard tissues. In particular, the formation processes of minerals can be partly replicated by utilizing bioinspired artificial materials to mimic the functions of biomolecules or stabilize intermediate mineral phases involved in biomineralization. Here, we review recent advances in biomineralization-inspired materials developed for hard tissue repair. Biomineralization-inspired materials are categorized into different types based on their specific applications, which include bone repair, dentin remineralization, and enamel remineralization. Finally, the advantages and limitations of these materials are summarized, and several perspectives on future directions are discussed.